Factors affecting the debt repayment behavior of the Fund of Empowerment of Persons with Disabilities in Nakhon Ratchasima province - บุญชัยสุข ศิริลักษณ์; แจ้งคล้อย อุษณา (KKBS Journal of Business Administration and Accountancy, 2019)
The purpose of this study was to examine and compare factors affecting debt repayment behavior of borrowers of the Fund for Empowerment of Persons with Disabilities in Nakhon Ratchasima Province. The data were collected from debtor’s database system of The Fund of Empowerment of Persons with Disabilities. The samples were 1,191 borrowers who had an obligation to repay the amount in fiscal year 2559 (A.D. 2016). Descriptive statistics were used to describe the basic features of the data. For the hypotheses testing, t- test and F-test were compiled to compare the differences between debt repayment behaviors and the six factors; gender, age, borrowing by the person with disabilities or the caregiver, types of disability, career, and the loan agreement term. The results of this study found that the samples consisted of 53.74 percent female. Most of the samples were self-borrower who had mobility or physical disability, aged between 41-50 years old. Their occupation was agricultural 48.3 percent and the majority of the samples, 39 percent, were the first year borrower. Factors affecting the differences of the debt repayment behavior at the statistically significant confidence level of 95 included the occupation factor and the loan agreement term. The rest; gender, age, status of the borrower, type of disability; were statically insignificant difference to the debt repayment behavior.